Solasodine-3-O-β-d-glucopyranoside kills Candida albicans by disrupting the intracellular vacuole. (August 2017) - Chang, Wenqiang; Li, Ying; Zhang, Ming; Zheng, Sha; Li, Yan; Lou, Hongxiang
Abstract: The increasing incidence of fungal infections and emergence of drug resistance underlie the constant search for new antifungal agents and exploration of their modes of action. The present study aimed to investigate the antifungal mechanisms of solasodine-3- O -β-d -glucopyranoside (SG) isolated from the medicinal plant Solanum nigrum L. In vitro, SG displayed potent fungicidal activity against both azole-sensitive and azole-resistant Candida albicans strains in Spider medium with its MICs of 32 μg/ml. Analysis of structure and bioactivity revealed that both the glucosyl residue and NH group were required for SG activity. Quantum dot (QD) assays demonstrated that the glucosyl moiety was critical for SG uptake into Candida cells, as further confirmed by glucose rescue experiments. Measurement of the fluorescence intensity of 2′, 7'-dichlorofluorescin diacetate (DCFHDA) by flow cytometry indicated that SG even at 64 μg/ml just caused a moderate increase of reactive oxygen species (ROS) generation by 58% in C. albicans cells. Observation of vacuole staining by confocal microscopy demonstrated that SG alkalized the intracellular vacuole of C. albicans and caused hyper-permeability of the vacuole membrane, resulting in cell death. These results support the potential application of SG in fighting fungal infections and reveal a novel fungicidal mechanism. Graphical abstract: Highlights: Glucosyl moiety mediates the uptake of SG into C. albicans cells. SG displays fungicidal action against C. albicans. SG elicits the dysfunction of C. albicans vacuoles and causes cell death.